COVID-19: a new turning point for dental practice - Flávio Freitas MATTOS; Isabela Almeida PORDEUS (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract Recent new zoonotic respiratory viruses have infected humans and led to severe acute respiratory syndrome: severe acute respiratory syndrome coronavirus (SARS-CoV), influenza A H5N1, influenza A H1N1 and Middle East respiratory syndrome coronavirus (MERS-CoV). The first SARS-CoV outbreak took place in 2003, in Guangdong, China. A decade later, another pathogenic coronavirus, MERS-CoV caused an endemic in Middle Eastern countries. The latest pandemic coronavirus infectious disease (COVID-19) has been related to the newly isolated severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). For the first time since the acquired immunodeficiency syndrome (AIDS) in the 1980s. Dentistry is facing a new turning point. This critical review aims to discuss the impact of COVID-19 infection on oral health care. In dental practice COVID-19 patients are the main source of infection and symptomatic patients are more contagious. Dentists can be first line of diagnosis of the disease, as they work in close contact with patients and are at the risk of being affected by COVID-19 and all respiratory infections. Several guidelines for dental practice environments have been published by dental associations and regulatory boards. It is already evident that biological, psychological and social effects of the COVID-19 pandemic have present and future impacts on dental practice. Dental schools, regulatory boards, scientific associations, government authorities, and public and private health care services must join efforts to design enduring answers for severe and long-standing viral challenges.